(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This research is motivated by one of the Physical Education subject matters that elementary school students must master. One of the floor exercise movements that is important for students to learn is the front roll. The front roll is a movement of rolling the body forward by relying on the nape, back, waist and pelvis in sequence. The demonstration learning model is a learning model that has the potential to overcome problems. The demonstration learning model emphasizes direct demonstration by the teacher regarding the steps or stages in carrying out a skill regarding the demonstration learning model. The general aim of this research is to examine the effect of applying the demonstration learning method and improving front roll learning outcomes. The method that the author uses in this research to test the truth of the hypothesis that has been proposed is the experimental method. The population in this study was male students in class V at SD Negeri Darmaraja 1, totalling 30 people, and the author used a sample of 30 people in this study. This research data was collected through a front roll test.